Caregiving consequences in cancer family caregivers: a narrative review of qualitative studies - Rezaei, Masoud; Keyvanloo Shahrestanaki, Sahar; Mohammadzadeh, Razieh; Aghili, Mohammad Sadegh; Rajabi, MohammadReza; Abbasi, Mohammad; Khachian, Alice; Momen, Reza; Khavassi, Mohammad; Aghaei, Simin (Frontiers in Public Health, 2024)
Background Cancer is a significant public health issue, causing various challenges for individuals affected by it. As cancer progresses, patients often become dependent on others for support. Family caregivers and members play a crucial role in the recovery and rehabilitation of these patients. However, caregivers themselves face numerous challenges throughout the course of their family member’s illness. Exploring the experiences of family caregivers can inform long-term planning and supportive interventions to address their caregiving difficulties. This study reviews previous literature on caregiving outcomes. Method This study presents a narrative review of qualitative studies, analyzing a total of 23 articles. The results were extracted and organized into subcategories. After revision by the research team, main categories were identified. These categories encompass both positive and negative outcomes of caregiving. Results The findings of this review demonstrate that caring for a family member with cancer has significant implications for caregivers. These implications include: (A) Positive outcomes of caregiving (such as achieving self-management and balance, promoting kinship intimacy, finding meaning and purpose, and experiencing spiritual growth) and (B) Negative outcomes of caregiving (including care-related physical exhaustion, disruption of personal life plans, psycho-emotional consequences, and socio-economic burden). Conclusion The results of this study highlight the challenges faced by family caregivers and emphasize the importance of addressing their needs within the healthcare system. By providing support and attention to their well-being, caregivers can enhance their resilience and adaptability in managing caregiving difficulties.